THE INFLUENCE OF THE TOURISM SECTOR ON ECONOMIC GROWTH AND ITS EFFECT ON MICRO AND SMALL ENTERPRISES (UMK) IN YOGYAKARTA - oeliestina oeliestina (Universitas Airlangga, 2021)
Yogyakarta’s economic growth contracted by up to 6.74 percent (Quarter II 2020). This is due to the declining growth of the tourism sector as the driving sector for Yogyakarta’s economy. Even though the tourism sector is the lifeblood of Micro and Small Enterprises (UMK). As many as 75.09 percent of Micro and Small Enterprises (UMK) are businesses that surround the Yogyakarta tourism sector which is usually invaded by tourists. The purpose of this research is to look at the impact of the tourism sector on economic growth and link it to Micro and Small Enterprises (UMK). The results of the Mc Nemar statistical test stated that the covid-19 pandemic affected Yogyakarta’s economic groth with a significance of 0.021. The results of the F-test indicate that the tourism sector (represented by Room Occupancy Rate variable (X1) and foreign guest visits (X2) affect economic growth (Y) with a significance of less than 0.05. The results of the literature method also add information that there are 3 Micro and Small Enterprises (UMK) who play an important role in Yogyakarta tourism, namely : the food industry, the weaving industry and the apparel industry (batik craft).